POLITIK EKSPANSI SULTAN AGUNG DI WILAYAH TIMUR TANAH JAWA 1614-1625 M - Nurul Lailia; Dwi Susanto (Qurthuba: The Journal of History and Islamic Civilization, 2022)
Abstract: Sultan Agung is the third king of the Mataram Kingdom who has brought Mataram to the peak of its glory. One of his successes was to expand his territory in various regions in Java, one of which was in East Java through the politics of expansion. This study aims (1) determine the condition of the Islamic Mataram Kingdom under the reign of Sultan Agung (2) explain the expansion politics carried out by Sultan Agung in the eastern region of Java, (3) analyze the strategy of Sultan Agung in carrying out the expansion policy in the eastern region of Java. This research uses qualitative research methods by collecting data sources through literature study. The results are (1) The leadership of Sultan Agung has brought Mataram to rapidly develop into the largest kingdom in Java and the archipelago in 1614-1645. This proves that Sultan Agung brought Mataram to excel in several fields such as politics, territorial expansion, economy, and religion (2) Beginning in 1614, Sultan Agung launched his first military attack on eastern Java as a political target for his expansion. Then in 1615-1625, Sultan Agung succeeded in conquering East Java areas such as Wirasaba, Siwalan and Lasem, Pasuruan, Tuban, and Surabaya (3) The expansion strategy to East Java was to understand the road, understand the seasons and weather, control the terrain, give command , and disciplined on the rules of the war leader. Keywords: Mataram, Sultan Agung, Expansion Politic, East Java